Pemberdayaan Ekonomi Kreatif Ibu PKK dalam Pembuatan Meja dan Kursi dengan Pemanfaatan Limbah Plastik - Erham As’ari; Yusuf Syiakhoni; Ani Nafisah; Irhamudin Irhamudin (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
This article is about community empowerment in making tables and chairs by utilizing plastic waste, this empowerment is carried out on a group of PKK women. The purpose of this assistance is to improve skills and realize the work of batik-patterned chairs by utilizing inorganic waste in the context of empowering the creative economy. The focus of the study of this article is how is the form of empowering the creative economy of PKK women in making tables and chairs using plastic waste? This assistance prioritizes the utilization of the potential and assets that already exist in the community. To be able to carry out the mentoring program, the steps used in this mentoring activity are Asset Based Community Development (ABCD). The result of this empowerment is that the use of plastic waste is used as a material for making ecobricks. Ecobricks are plastic drink bottles packed with non-organic waste to make reusable building blocks.